2020
DOI: 10.1093/humupd/dmz040
|View full text |Cite
|
Sign up to set email alerts
|

Long-acting reversible contraception immediately after medical abortion: systematic review with meta-analyses

Abstract: BACKGROUND Long-acting reversible contraceptives (LARCs) are safe, effective and convenient post-abortal methods. However, there is concern that some LARCs may reduce the effectiveness of abortifacient drugs or result in other adverse outcomes. OBJECTIVE AND RATIONALE We undertook two systematic reviews to examine the early administration of LARCs in women undergoing medical abortion with mifepristone and misoprostol. (i) For… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 16 publications
1
24
0
Order By: Relevance
“…The ENG-releasing subdermal implant could be employed immediately after a surgical abortion [190][191][192] or on the same day of mifepristone assumption, without an increase in pregnancy risk compared to the delayed placement 4-8 weeks after the procedure [195][196][197]199]. It has been shown to be effective in improving symptomatic endometriosis with reduction in pain severity and menstrual symptoms (dysmenorrhea and dyspareunia) [201,210,211]; ENG therapeutic efficacy for pain relief is not inferior to other progestins [209,210].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ENG-releasing subdermal implant could be employed immediately after a surgical abortion [190][191][192] or on the same day of mifepristone assumption, without an increase in pregnancy risk compared to the delayed placement 4-8 weeks after the procedure [195][196][197]199]. It has been shown to be effective in improving symptomatic endometriosis with reduction in pain severity and menstrual symptoms (dysmenorrhea and dyspareunia) [201,210,211]; ENG therapeutic efficacy for pain relief is not inferior to other progestins [209,210].…”
Section: Discussionmentioning
confidence: 99%
“…In a retrospective study, Park et al [198] demonstrated that the administration of a progestin-based contraceptive such as an ENG implant or DMPA injection on the same day as mifepristone for medical abortion did not alter the successful abortion rates [198]. In a recent systematic review and meta-analysis, Schmidt-Hansen et al [199] showed that after abortion, the risk of subsequent unintended pregnancy was lower for patients treated with the etonogestrel implant simultaneously with mifepristone compared to delayed treatment both after three (risk ratio = 0.10; 95% CI, 0.01 to 1.94; p = 0.13) and six months (risk ratio = 0.22; 95% CI, 0.06 to 0.78; p = 0.02). Therefore, in women undergoing pharmacological pregnancy termination, contraceptive implant insertion should be offered on the day of mifepristone [199].…”
Section: Post-abortion Implant Placementmentioning
confidence: 99%
“…44 Alternatively, this may also be observed due to contraception indications at the time of taking mifepristone for medical abortion when the implant is the only suitable LARC option. 79 Preference for non-LARC methods or no contraception was associated with relative socioeconomic disadvantage compared with those preferring LARC, and the belief that LARC methods are ineffective, among a sample of mostly African-American and Latinx pregnant adolescents. 62 These participants reported experiences typically congruous with poorer contraceptive self-efficacy, including not discussing contraception with parents and not perceiving themselves as autonomous decision-makers.…”
Section: Discussionmentioning
confidence: 95%
“…The increase in uptake of IPA LARC methods, driven by contraceptive implant availability in New Zealand, could also reflect adolescents’ preference for this method over Cu‐IUD/LNG‐IUS 44 . Alternatively, this may also be observed due to contraception indications at the time of taking mifepristone for medical abortion when the implant is the only suitable LARC option 79 …”
Section: Discussionmentioning
confidence: 99%
“…Most induced abortions were performed in the first trimester. [ 2 ] Induced abortion in the first trimester could be performed surgically (by manual or electric vacuum aspiration) or with medication. Though both methods have similar complete abortion rates, medical abortion is more natural and less harmful for its simplicity of operation.…”
Section: Introductionmentioning
confidence: 99%